Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Inpirasi Bisnis Nusantara Area Tangerang Selatan - Siti Kholifah, Laili; Astuti, Widia (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
Abstrak. This study aims to determine the effect of work discipline (X1) and work motivation (X2) on employee performance (Y) at PT Inspirasi Bisnis Nusantara. The research method used is a quantitative method with an associative approach, where data collection is carried out by distributing questionnaires to 55 respondents who are employees of PT Inspirasi Bisnis Nusantara. The research instrument was first tested for validity and reliability before being used. Data analysis techniques applied include descriptive analysis, classical assumption tests, correlation analysis, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). Quantitative analysis uses t-test and F-test. The results of the t-test show that the work discipline variable (X₁) has a significant effect on employee performance (Y) with a value (t count 31.524> t table 1.672), a significance value (0.000 <0.05). And work motivation (X₂) also has a significant influence with a value (t count 24.211> t table 1.672), a significance value (0.000 <0.05). While the results of the F test show that simultaneously both X variables have a significant influence on Y with a value (F count 597.653> F table 3.16) and a significance value (0.000 <0.05). The R-square value (coefficient of determination) simultaneously or together is 0.954, which means that work discipline (X1) and work motivation (X2) together contribute to the influence on employee performance (Y) by 95.4%, while the remaining 4.6% is influenced by other factors not studied Keywords: Employee Performance, Work Discipline and Work Motivation